Semantika produk kacamata dan hubungannya dengan pencitraan kader politik - Abbyzar Raffi Hernawan; Achmad Syarief (Institut Seni Indonesia Yogyakarta, 2021)
Daily use objects form someone’s self-image as it mark the appearance of identify, life style and character of a person. Therefore, owned and used objects hold a role of persuasion tool. This well-aware knowledge is deliberately used in political campaign such as posters, baliho, and banners which present image of a political candidate. The appeal of blazer, shirts, eyeglasses, moslem hijab and cap, serves as means to develop self-image and character, especially when it is amplify competent image of an intellectual that hold leadership, and honesty. Using semanic differential method, the research analyze varieties of type, forms/shapes, and physical measurement of eyeglasses; in order to understand perceptual varieties of self-image that openly appear in public